Seafood science : advances in chemistry, technology, and applications - Kim, Se-Kwon. (Boca Raton : CRC Press/Taylor & Francis, 2015)
'Preface Seafood is simply'food from the sea'. It comes in various forms and is used as food for human beings. Seafood predominantly includes fish, crustaceans, mollusks and seaweeds. It is one of the important sources of protein and nutrients for human health. This book contains a total 21 chapters. Chapter 1 provides a general introduction to the topics covered in this book and also the seafood production statistics around the globe. Chapter 2, 4 and 7 give information related to seafood processing methods such as fermentation, cooking, and MALDI-TOF for the seafood production and safety assessment. Chapter 5, 6, 8 and 10 cover fish protein and fish oil. Chapter 11 deals about chitosan as bio based nanocomposites in seafood industry and aquaculture. Chapter 14, 15 and 16 deal with seaweed production and their applications. Chapter 17 and 18 cover the biological application of seafood in food industry. Chapter 19 and 21 describe the health benefit value and discuss health risk of seafood. Overall, this book provides details about seafood (fish, crustaceans, mollusks and seaweed) processing methods, biological applications, health benefits and health risk. These contributions will form essential reading for seafood scientists and can serve as instructional course for students. I am grateful to all the authors who have provided the state-of-art contributions in the field of seafood. Their relentless effort was the result of scientific attitude, drawn from the past history in this field. Busan, South Korea Prof. Se-Kwon Kim'--
Keywords: Seafood; Food -- Composition; Fishery processing; Fisheries